Neuroprotection Exerted by Netrin-1 and Kinesin Motor KIF1A in Secondary Brain Injury following Experimental Intracerebral Hemorrhage in Rats - Wang, Jun; Zhai, Weiwei; Yu, Zhengquan; Sun, Liang; Li, Haiying; Shen, Haitao; Li, Xiang; Liu, Chunfeng; Chen, Gang (Frontiers in Cellular Neuroscience, 2018)
Binding of extracellular netrin-1 to its receptors, deleted in colorectal cancer (DCC) and uncoordinated gene 5H2 (UNC5H2), inhibits apoptosis mediated by these receptors. A neuron-specific kinesin motor protein, KIF1A, has been shown to participate in netrin-1 secretion. This study aimed to identify the roles of netrin-1 and KIF1A in secondary brain injury after intracerebral hemorrhage (ICH) and the potential mechanisms. An autologous blood ICH model was established in adult male Sprague-Dawley rats, and cultured neurons were exposed to OxyHb to mimic ICH conditions in vitro. Mouse recombinant netrin-1, expression vectors encoding KIF1A, and KIF1A-specific siRNAs were administered intracerebroventricularly. After ICH, protein levels of netrin-1, DCC, and UNC5H2 increased, while protein levels of KIF1A decreased. Levels of UNC5H2 and DCC bound to netrin-1 increased after ICH but were significantly lower than the increase in total amount of protein. Administration of recombinant netrin-1 attenuated neuronal apoptosis and degeneration in ICH rats. Moreover, KIF1A overexpression increased concentrations of netrin-1 in cerebrospinal fluid and cell culture supernatant and exerted neuroprotective effects via netrin-1 and its receptor pathways. KIF1A plays a critical role in netrin-1 secretion by neurons. An increase in protein levels of netrin-1 may be a neuroprotective strategy after ICH. However, this process is almost completely abolished by ICH-induced loss of KIF1A. An exogenous increase of KIF1A may be a potential strategy for neuroprotection via the netrin-1 pathway.